Role Of Peroxynitrite In Diabetic Neuropathy: Peroxynitrite Decomposition Catalysts - SAMPATH KUMAR.V; LINGESH.A; BHASKAR.B; UPENDER.A (International Journal of Pharma and Bio Sciences, 2011)
Diabetes is a major problem in the world. Diabetic complications, due to the persistent hyperglycemia, involves formation of reactive oxygen species (ROS) from various pathways like, increased flux of glucose to polyol pathway, aldose reductase activation, formation of advanced glycation end products(AGE), activation of protein kinase-C(PKC) and activation of poly(ADP-ribose) polymerase. Peroxynitrite is the most potent reactive oxygen species (ROS) and studies have shown that it is capable of oxidizing the proteins, non-proteins and nucleotides. It may lead to cell death and tissue injury. Peroxynitrite is implicated in sensory and motor nerve deficits in rodent models. Peroxynitrite reacts too slowly with endogenous reducing agents, but, very efficiently with synthetic metalloporphyrins. Peroxynitrite decomposition catalysts correct the sensory and motor nerve deficits in rodents. Present review focuses on the beneficial effects of peroxynitrite decomposition catalysts in experimental diabetic neuropathy.